Analisis Potensi dan Minat Masyarakat Dalam Program Badan Usaha Milik Desa Murni Jaya Di Desa Sumbermulyo Kabupaten Jombang Tahun 2021 - Kurniawati, Siti Ria; Jaelani, Ahmad Fajar; Dardiri, Masyhudan (Dinamis: Jurnal Pengabdian Kepada Masyarakat, 2022)
Murni Jaya Village Owned Enterprise is a business entity owned by Sumbermulyo village with the Basis of Establishing BUMDes Murni Jaya according to Village Regulation/Perdes Number 2 of 2015 concerning Establishment of Pure Jaya BUMDes in Sumbermulyo Village and Minister of Village Regulation Number 4 of 2015. The research method used in This research is aqualitative research with a descriptive approach, with the research focus: 1. Village potential, 2. Village community interest, 3. Inhibiting and supporting factors. The results of this study are the potential and interest of the village community towards the Murni Jaya Village Owned Enterprise program in Sumbermulyo Village, Jombang Regency. In the next few years, the Murni Jaya Village-Owned Enterprise will add several fields of tourism business to increase village income. However, there is one line of business that is currently underdeveloped and generates income for village income. So it can be said that the existence of this Pure Jaya Village Owned Enterprise is very good.